Malaysia’s Rural Health Development: Foundation of Universal Health Coverage - Wong, Justen Han Wei; Ng, Chiu Wan; Su, Tin Tin (Penerbit Universiti Kebangsaan Malaysia, 2019)
From 101 records relating to health kept in the National Archives of Malaysia for the period 1946–1981, 30 records were chosen using purposive criterion-based sampling on dimensions of universal health coverage (UHC) and health system governance. From those 30, document review was performed on 13 records that were selected based on relevance to analysis of the evolution of private and public health institutions and their roles in achieving UHC from 1946 to 1981. UHC relates to the ability of patients to access good quality service with high population coverage of health care at low financial risk. Malaya was a former Western Pacific nation ruled by the British colonial government. Initially, the government bore the cost of medicines and passages between the United Kingdom and Malaya for Red Cross and St. John’s ambulance teams to serve in rural areas in Malaya. This was later replaced by home grown Rural Health Teams trained in purpose built Rural Health Centres beginning with the first such training school in Jitra under the Rural Health Scheme. The Rural Health Scheme was implemented from 1953 to 1956 and marked an ambitious period of utilising limited resources to expand human resource and establish District Health Centres, Sub-District Health Centres, Midwives’ Houses and Maternal and Child Health Centres across the rural landscape of Malaya. After analysis, it was found that the British colonial government’s efforts in improving public health through the Rural Health Scheme had provided the foundation for achieving UHC in Malaysia today.